COMPETITIVENESS OF PERUM PERHUTANI CAJUPUT OIL IN ACHIEVING SUSTAINABLE DEVELOPMENT GOALS IN THE FORESTRY SECTOR - Rochman, Noor; Nugroho, Bramasto; Trison, Soni; Malik, Jamaludin (Indonesian Journal of Forestry Research, 2026)
Cajuput (Melaleuca cajuputi) oil is one of the products developed under Perum Perhutani’s Multipurpose Forestry Business. Developing the cajuput oil business remains a challenge; efforts must continue to build both competitive and comparative advantages and to increase revenue. The aim of this research is to analyze the competitiveness of Perum Perhutani's cajuput oil business which can be managed in accordance with the concept of sustainable development goals in the Forestry Sector. In doing this, we use Resources Based Value (RBV) and Value, Rarity, Imitability, and Organization (VRIO) analysis to evaluate the competitive resouces of cajuput oil bussines. SmartPLS was used to test the influence on achieving the Sustainable Development Goals (SDGs). The results show Perum Perhutani has sustainable competitive advantages, namely the quality of its cajuput oil plant seeds, the ability to achieve supply chain certification, and the ability to produce good quality products sustainably. In running the cajuput oil business, Perum Perhutaniexperiences a significant impact from applying SDG values, which manifest as both economic and ecological benefits.. Perhutani’s cajuput oil products are more competitive than those of other domestic producers, but less competitive when compared to imported eucalyptus oil products in the global market.